What Keeps the Family Caregiver Motivated to Care for Their Dying Relative at Home? A Brief Report of a Qualitative Interview Study - Julia Strupp; Alina Kasdorf; Jonas Karneboge; Raymond Voltz (Palliative Medicine Reports)
Background: Dying at home poses many challenges for family carers and is particularly distressing for those with limited social support. In addition to financial hardship, this perceived burden may be a deciding factor in providing care at home. Aims: To explore what motivates people to provide care at home until death. Methods: Qualitative interviews with 43 family carers of deceased patients about factors enabling death at home. Interviews were audio-recorded, transcribed verbatim, and analyzed using content analysis. Results: Participants who rated their end-of-life experience positively reported that they particularly benefited from encouraging feedback and gratitude from their dying loved ones, as well as appraisal support. It takes courage to care for someone at home and to feel responsible for them. These themes made the participants’ home care efforts meaningful, gave them confidence in what they were doing and helped maintain their motivation to care. Conclusion: Encouraging feedback and appraisal support are both minimally invasive techniques with maximum impact for continuing care at home.